(untitled) (The Review of Diabetic Studies, 2024)
Background: Nursing staffing levels have a significant impact on patient outcomes, including patient safety, satisfaction, and overall care quality. In Saudi Arabia, the shift towards privatized healthcare settings has introduced challenges related to nurse staffing, which may influence patient care. Despite the growing body of research on nurse staffing, limited studies specifically address the relationship between staffing levels and patient outcomes in Saudi Arabia’s privatized healthcare system. Aim: This systematic review aims to explore the relationship between nursing staffing levels and patient outcomes, focusing on privatized healthcare settings in Saudi Arabia. The review seeks to assess how nurse staffing, nurse engagement, and work environment influence patient care quality and safety. Method: A comprehensive search was conducted across multiple databases, including PubMed, CINAHL, Scopus, Google Scholar, and ProQuest, for studies published between 2020 and 2024. Ten studies were selected based on their relevance to the research question and methodological quality. The studies included in the review were primarily cross-sectional and observational studies, focusing on nurse staffing and its impact on patient outcomes. Results: The review found that adequate nurse staffing levels are directly associated with improved patient safety, reduced medical errors, and higher patient satisfaction. In contrast, inadequate staffing was linked to adverse outcomes such as increased patient morbidity, longer hospital stays, and higher mortality rates. Nurse engagement and job satisfaction also played a critical role in improving patient outcomes, while burnout and turnover negatively affected care quality. Conclusion: Adequate nurse staffing is essential for ensuring optimal patient outcomes in privatized healthcare settings. Policymakers should prioritize evidence-based staffing models to enhance care quality and patient safety in Saudi Arabia’s evolving healthcare system.